On the space of multipliers and convolutors in the space of tempered ultradistributions - Dimovski Pavel; Prangoski, Bojan; Velinov, Daniel (Department of Mathematics and Informatics, Faculty of Sciences, University of Novi Sad, Serbia, 2014)
We consider the space of convolutors and the space of multipliers of Beurling and Roumieu tempered ultradistributions and we give characterization theorems for them.